PERILAKU AGRESIF ANGGOTA ORGANISASI EMASYARAKATAN (ORMAS) â€œXâ€ DI PROVINSI D.I. YOGYAKARTA - Ibnu Sutowo; Susilo Wibisono (Universitas Ahmad Dahlan, 2013)
AbstractThis research is aimed to understand psychological dynamics ofaggressive behaviors among the social organizationâ€™s membersinJogjakarta. This research usedqualitative approach. Respondents were the active members of the social organization (ormas) â€œXâ€ in Jogjakarta. The result shows some factors that influence the aggressive behavior among the members, which are group influence, deindividuation, frustration, drug or alcoholic and physical environmental. The aggressive behaviors were done by the members of ormas â€œXâ€are included physical and verbalaggression. Physical aggressionswere done by member of ormas â€œXâ€such as destruction of public facilities, injuring another person and inter-group conflict. Verbal aggressionswere done by member of ormas â€œXâ€such as harassment, oppression and intimidation to the victims. The aggressive behaviors among the member of ormas X were done spontaneously. On the other hand, aggression done by ormas â€œXâ€ to other organization or group also includes an invisibility aggression such as refusing to supportother organization, rejection from agreement, and boycott the otherâ€™s activities.Keywords: aggressive behavior, social organization (ormas).